2006
DOI: 10.1248/bpb.29.1962
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Mitochondria during the Cell Cycle

Abstract: As well as the classic bean-shaped structures observed in electron micrographs, mitochondria are frequently found as long, snake-shaped tubules, and extended reticular networks whose overall morphology depends on the balance of fission and fusion of mitochondrial tubules in growing cells. [1][2][3][4] Such mitochondrial morphology, size, distribution, and copy number were demonstrated to change in living cells during cellular differentiation, development, or under pathological conditions, including liver disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
1
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 21 publications
2
34
1
3
Order By: Relevance
“…Cell cycle-dependent morphological changes of mitochondria were first reported by Arakaki et al [20]. We also showed that mitochondria exist as highly inter-connected tubular structures or long spiral forms of tubules during interphase but undergo a drastic reorganization upon mitotic entry.…”
Section: Discussionsupporting
confidence: 69%
“…Cell cycle-dependent morphological changes of mitochondria were first reported by Arakaki et al [20]. We also showed that mitochondria exist as highly inter-connected tubular structures or long spiral forms of tubules during interphase but undergo a drastic reorganization upon mitotic entry.…”
Section: Discussionsupporting
confidence: 69%
“…Several recent reports have shown that changes in mitochondrial morphology occur during cell division (Arakaki et al, 2006;Lee et al, 2007) and that Drp1 is phosphorylated by Cdk1-cyclin B in this process (Taguchi et al, 2007). We show that overexpression of MTGM results in mitochondrial fragmentation, stalling of cells in S-phase-associated DNA damage indicated by γ-H2AX staining, and exclusion of cells from mitosis, whereas depletion of MTGM results in mitochondrial elongation and cell-cycle progression.…”
Section: Discussionmentioning
confidence: 50%
“…These processes not only control the shape of mitochondria but also affect many cellular functions (Chan, 2006;Grandemange et al, 2009;Knott et al, 2008;Suen et al, 2008). Several recent studies reported that morphological changes of mitochondria occur during cell division (Arakaki et al, 2006;Lee et al, 2007). Mitochondria present as interconnected tubular structures in interphase, undergo a drastic reorganization and fragmentation at an early mitotic stage, and finally reform tubular structures in the two daughter cells.…”
Section: Introductionmentioning
confidence: 99%
“…Although attempts have been made to investigate this question (7,8), no study has been conclusive enough to determine whether changes in mitochondrial morphology are determinant of any cell cycle stage. These cell cycle stages include a long growth phase (G 1 ), a DNA replicating phase (S), a short growth phase (G 2 ), and cell division (mitosis, M).…”
mentioning
confidence: 99%